Association of Interleukin-10 Genotypes and Oral Cancer Susceptibility in Selected Malaysian Population: A Case- Control Study - Goud, E V Soma Sekhar; Malleedi, Shanthi; Ramanathan, Anand; Wong, Gou Rean; Hwei Ern, Beatrix Tan; Yean, Goh Yin; Ann, Ho Hui; Syan, Tan Yuen; Zain, Rosnah (West Asia Organization for Cancer Prevention, 2019)
Background: Interleukin-10 (IL10) genotypes have been closely correlated to the susceptibility for oral squamous cell carcinoma. More than half of oral cancers in the world occur in Asia with estimated 168,850 new cases were diagnosed in this geographical region alone. Considering the rising numbers of oral cancer cases in Malaysia, association of IL10 A1082G gene polymorphism was correlated. Methodology: 41 oral squamous cell carcinoma (OSCC) cases and 48 healthy controls of comparable age, gender, and with habits like smoking, alcohol consumption and betel quid chewing were selected. In this case-control study, samples were collected from the Oral Cancer Research and Coordinating Centre (OCRCC), Faculty of Dentistry, University of Malaya, Malaysia. Genotyping conditions were evaluated by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP). The PCR products were subjected to digestion by MnlI enzyme (NEB, UK) to screen for the IL10 A-1082G. Digested DNA products were analyzed by electrophoresis on 4% (w/v) agarose gel, stained with ethidium bromide and imaged under UV illumination. Chi-square test and Fisher's Exact test were used in statistical analysis. Results: AG genotypes were present in 81.3% and 86.0% of healthy control and OSCC cases respectively (OR=0.468, 95% CI=0.133-1.653). No significant association was found between IL10 A1082G polymorphism with risk habits, clinico-pathological parameters and 5-years overall survival. The findings also show no significant correlation between the IL10 genotype and features of OSCC within the case group as measured by tumor size, lymph node involvement, stage, invasive front, grading, depth, pattern of invasion. Conclusion: This study suggests that functional polymorphism AG of IL10 A1082G may have no influence with OSCC susceptibility. However, further investigation with larger sample sizes can be conducted to provide additional evidence to support the lack of association of IL10 A1082G polymorphism in oral cancer. © 2019 IL10 Gene Polymorphism in Oral Cancer.